Algae Oil Extraction from Freshwater Microalgae Chlorella Vulgaris - Nurfarahanim, Abdullah; Nur Amelia, Amran; Nur Hidayah, Mat Yasin (The Malaysian Analytical Sciences Society, 2017)
This research aims to investigate the optimum condition of oil extraction method to extract maximum oil yield from freshwater microalgae Chlorella vulgaris. The modified soxhlet extraction method was used to identify the best solvent systems which are heptane, heptane: methanol (1:1), heptane: methanol (1:2), heptane: ethanol (1:1) and heptane: ethanol (1:2) for extracting the microalgae oil. The effect of different mixing rate (rpm), temperature (oC) and extraction time (hours) were carried out using the optimized solvent system to evaluate the optimum condition of oil extraction. Based on the yield of oil extraction, heptane alone become the best solvent to extract the oil with the yield of 57.5%, followed by heptane: methanol (1:2), heptane: ethanol (1:1), heptane: ethanol (1:2) and heptane: methanol (1:1) with the yield of 47.5%, 44.8%, 43.2% and 41.4%, respectively. Maximum oil quantity of 61.27% was obtained after extracted the Chlorella vulgaris biomass using heptane as a solvent at the following optimal conditions: mixing rate of 600 rpm, temperature of 65 °C and extraction time of 5 hours. This study confirmed that an increasing temperature resulted in the increased of oil yield, but at higher temperature (greater than 65 °C), the oil yield was decreasing. Too high of temperature in oil extraction may cause partial decomposition of the microalgae cells and thus lowering the yield of oil extracted.